Pemilihan Supplier Pangan Organik dengan Metode Analytic Network Process (ANP) - Nur Izzaty; Alma Arif; Raihan Dara Lufika (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2024)
Supplier selection is one of the activities in the flow of supply chain and strategic decisions that can increase the competitive advantages for the company. AF organic shop is a business engaged in the organic food industry. There are several problems related to supplier selection due to the less optimal performance of each supplier. This study employed Analytic Network Process (ANP) method and assisted with the Software Super Decisions in order to determine the primary criteria and sub-criteria in the process of supplier selection, adjusted to the requirements of AF by comparing various feedbacks regarding each supplier against the specified criteria to achieve company goals. The results revealed that the order of the essential criteria for AF’s suppliers sequentially are quality (0.417), price (0.360), service (0.159), and delivery (0,070). Meanwhile, the primarily subcriteria considered supplier selection was the conformity of products and specifications with the score 0.739. Quality criteria is the most important focus for AF since it committed to maintain the quality of organic food ingredients sold to consumers. Therefore, it indicated that the best supplier was WSM with the score 0.446.